Your money milestones : a guide to making the 9 most important financial decisions of your life - Milevsky, Moshe Arye, 1967- (FT Press, 2010)
A Whole New Way to Look at Your Money...and Make It Grow! "Here is a lively new guide that offers fresh and actionable ways to approach everyday financial problems. Whether you're rich or just getting by, starting your career or winding down, you'll benefit from the author's insightful observations and suggestions--all delivered with warmth and wit." --Evan Cooper, Deputy Editor, InvestmentNews "The author's unique gift is to make complex ideas from the world of high finance simple to understand, and his new book gently coaches readers in how to think about their personal finances. Best of all, readers can use Milevsky's financial calculators online to test these ideas, so they can make choices with confidence. Investing in this book might be the wisest financial decision you make this year." --Gil Weinreich, Editor, Research Magazine "The author has accomplished the near impossible. He has made the complicated, confusing, and often contradictory world of personal financial planning easy to understand. More importantly, he's made it easy to act on his ground-breaking advice and guidance and has made it easy for readers to address their most important financial decisions in a thoughtful, practical, and painless manner." -- Robert Powell, Editor, Retirement Weekly and Retirement Columnist, www.MarketWatch.com/retirement "What are the nine crucial financial decisions every person must make over the course of a lifetime? If you don't know, read this book. The author's nine choices revolve around his core concept of human capital and how it must be gradually converted to financial capital to achieve a successful retirement." --Jonathan Chevreau, National Post Columnist and Author of Findependence Day " Your Money Milestones helps just about anyone see life's most important money decisions in a fresh and completely rational light. If you want a smart, practical roadmap to a financially sound future, you need this book." --Eric Schurenberg, Editor-in-Chief, BNET Your Money Milestones illustrates how four principles inspired by basic arithmetic can be applied to manage the most important financial decisions (money milestones) people face over their entire financial lifecycles. Addition : Identify the true value all of your financial resources. Subtraction : Budget for the hidden liabilities in your future. Division : Spend your total resources evenly over time. Multiplication : Prepare for many alternative and unexpected universes. This book offers a complete...